2015
DOI: 10.3390/su70912870
|View full text |Cite
|
Sign up to set email alerts
|

A Process for the Implementation of New Renewable Energy Systems in a Building by Considering Environmental and Economic Effect

Abstract: Abstract:The excessive use of fossil fuels has led to global warming and air pollution. To solve these problems, interest in new renewable energy system (NRE system) has increased in recent years. In particular, photovoltaic, solar thermal heating, fuel cell and ground source heating system are actively implemented for achieving the zero energy building. Since the initial investment cost of the NRE system is quite expensive, it is necessary to conduct a feasibility study from the life cycle perspective. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Based on the intensity of energy for aquaculture by regions, it is showed that Europe and Central Asia has the highest energy intensity with 0.032 TJ/ton, followed by others. The high energy intensity accounts for a large percentage of intensive culture or land-based system [5].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the intensity of energy for aquaculture by regions, it is showed that Europe and Central Asia has the highest energy intensity with 0.032 TJ/ton, followed by others. The high energy intensity accounts for a large percentage of intensive culture or land-based system [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the building energy consumption area, the use of HVAC (heating, ventilation and air conditioning) is the main way to meet increasing residential comfort requirements and accounts for the vast majority of energy consumption, 50% in developed countries [8] and more than 60% in China [9]. Therefore, reducing the energy consumption of the HVAC system is the key to reducing building energy consumption and is an effective way to deal with the global energy crisis [10].…”
Section: Introductionmentioning
confidence: 99%
“…The combination system of PV and H 2 produced by water electrolyzer using renewable energy sources have been studied numerically as well as experimentally [8]- [23]. Energy and exergy analysis [8] [9] [10], economic assessment [11] [12] [13] [14] [15], environmental assessment [16] [17] and dynamic control procedure in a short time [18] [19] [20] were reported. Though the storage characteristics of H 2 produced by water electrolisys are investigated [21] [22], there are a few reports that investigate the transportation system of H 2 produced by water electrolysis using the power generated by renewable energy sources [3] [23], which are only discussed about CO 2 emission and more investigations are necessary from the viewpoint of energy assessment.…”
Section: Introductionmentioning
confidence: 99%